2011
DOI: 10.1111/j.1365-2982.2011.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased prokineticin 2 expression in gut inflammation: role in visceral pain and intestinal ion transport

Abstract: Elevated Prok2 levels, as a consequence of gastrointestinal tract inflammation, induce visceral pain via prokineticin receptors. This observation, together with the finding that PROK2 can modulate intestinal ion transport, raises the possibility that inhibitors of PROK2 signaling may have clinical utility in gastrointestinal disorders, such as irritable bowel syndrome and inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
(106 reference statements)
3
26
0
Order By: Relevance
“…Watson et al . found that elevated Bv8 expression in gut inflammation might contribute to visceral pain and ileal ion transport, which indicated that inhibitors of Bv8 signalling likely have clinical utility in inflammatory gastrointestinal disorders. Using the classical complete Freund's adjuvant‐induced inflammatory pain model, a previous study had demonstrated that Bv8 was involved in inflammatory pain .…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al . found that elevated Bv8 expression in gut inflammation might contribute to visceral pain and ileal ion transport, which indicated that inhibitors of Bv8 signalling likely have clinical utility in inflammatory gastrointestinal disorders. Using the classical complete Freund's adjuvant‐induced inflammatory pain model, a previous study had demonstrated that Bv8 was involved in inflammatory pain .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that visceral pain sensitivity intensified and pain threshold decreased in rats after the establishment of the model. A study by Watson et al [37] showed that PK2 gene expression in the gastrointestinal tract was significantly upregulated in ulcerative colitis patients and rodent models of colitis visceral pain induced by mustard oil, trinitrobenzene sulfonate, water-avoidance stress, and Citrobacter rodentium infection. Therefore, it was believed that enhanced PK2 expression induced visceral pain through the PKR2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking either PK2 or PKR1 genes displayed a significant reduction in nociception induced by noxious heat and various chemical stimuli such as capsaicin, protons and formalin [15,19]. Recently, Watson et al found that increased PK2 expression in gut inflammation likely contributes to visceral pain [20]. It has been shown that PKR1 and PKR2 are present in nociceptive primary sensory neurons [15,17].…”
Section: Introductionmentioning
confidence: 99%